Complementary alternative medicine use among patients with dengue fever in the hospital setting: a cross-sectional study in Malaysia - Ching, Siew Mooi; Ramachandran, Vasudevan; Gew, Lai Teck; Mohd Sazlly Lim, Sazlyna; Wan Sulaiman, Wan Aliaa; Foo, Yoke Loong; Zakaria, Zainul Amiruddin; Samsudin, Nurul Huda; Lau, Paul Chih Ming Chih; Veettil, Sajesh K.; Hoo, Fan Kee (BioMed Central, 2016)
Background: In Malaysia, the number of reported cases of dengue fever demonstrates an increasing trend. Since dengue fever has no vaccine or antiviral treatment available, it has become a burden. Complementary and alternative medicine (CAM) has become one of the good alternatives to treat the patients with dengue fever. There is limited study on the use of CAM among patients with dengue fever, particularly in hospital settings. This study aims to determine the prevalence, types, reasons, expenditure, and resource of information on CAM use among patients with dengue fever. Methods: This is a descriptive, cross-sectional study of 306 patients with dengue fever, which was carried out at the dengue clinic of three hospitals. Data were analysed using IBM SPSS Statistics version 21.0 and logistic regression analysis was used to determine the factors associated with CAM use. Results: The prevalence of CAM use was 85.3 % among patients with dengue fever. The most popular CAMs were isotonic drinks (85.8 %), crab soup (46.7 %) and papaya leaf extract (22.2 %). The most common reason for CAM use was a good impression of CAM from other CAM users (33.3 %). The main resource of information on CAM use among patients with dengue fever was family (54.8 %). In multiple logistic regression analysis, dengue fever patients with a tertiary level are more likely to use CAM 5.8 (95 % confidence interval (CI 1.62–20.45) and 3.8 (95 % CI 1.12–12.93) times than secondary level and primary and below respectively. Conclusion: CAM was commonly used by patients with dengue fever. The predictor of CAM use was a higher level of education.